ANALISIS PENGENDALIAN INTERNAL ATAS PERSEDIAAN DAN PEMBELIAN PADA PT. CATUR ANUGERAH SEJATI MEDAN - Rudyanto Simanjuntak; Monica Monica; Sunarji Harahap; Elidawati Elidawati (JURNAL BISNIS KOLEGA, 2020)
Abstract. The problem in this study is there is a concurrent position of employee doing the work of buying, paying, reporting usage and watch over the spareparts inventory warehouse and no approval before purchase which make purchase activity often being exchanged. The method used is observation, documentation, and study of literature. The object of research in this study is internal control, inventory and purchasing at PT. Catur Anugerah Sejati, Medan. The data analysis technique used is descriptive qualitative analysis. Results of research in the control environmental components, risk assessment, control activities, and monitoring are not good because it violates the regulations set by the company. The results of research in purchase for the control environment, risk assessment and monitoring components are not good because they have deficiencies that need to be corrected. Conclusion of this research is necessary to add more workers so the division of tasks can be carried out well and need to strict regulations so that workers do not make a purchase before getting approval from the head office.   Keywords: Internal Control, Inventory, Purchasing